The Effect of Endorphin Massage on Reducing Back Pain Intensity in Third-Trimester Pregnant Women at TPMB Luli Bahari, Purwakarta, 2026 - Sekar Larasati; Nova Rati Lova; Shinny Ria Pratiwi (Public Health Journal, 2026)
Back pain is a common problem experienced by pregnant women, particularly during the third trimester, due to natural bodily changes, weight gain, changes in balance, and stretching of muscles and ligaments. Endorphin massage is a non-pharmacological method that may help reduce this pain. This study aimed to determine the effect of endorphin massage on reducing back pain intensity among third-trimester pregnant women at TPMB Luli Bahari, Purwakarta, in 2026. A quantitative method with a quasi-experimental one-group pretest-posttest design was used. The study was conducted from January 15 to February 17, 2026, involving 30 third-trimester pregnant women. Back pain intensity was measured before and after endorphin massage. Data were analyzed using univariate and bivariate analyses, with the Wilcoxon Signed-Rank Test applied because the data were not normally distributed. Before the intervention, most respondents experienced moderate pain (22 respondents; 73.3%), while 5 respondents (16.7%) experienced mild pain and 3 respondents (10.0%) experienced severe pain. After the intervention, 25 pregnant women (83.3%) experienced mild pain, while 5 (16.7%) reported no pain. The Wilcoxon test produced a p-value of 0.001 (p < 0.05), indicating a significant effect of endorphin massage on reducing back pain intensity in third-trimester pregnant women. Endorphin massage can therefore be considered a non-pharmacological approach to help alleviate back pain during pregnancy.